Synthesis, in vitro and computational studies of 1, 4-disubstituted 1, 2, 3-triazoles as potential α-glucosidase inhibitors. Issue 3 (1st February 2016) - Jabeen, Farukh; Shehzadi, Syeda Aaliya; Fatmi, Muhammad Qaiser; Shaheen, Sobia; Iqbal, Lubna; Afza, Nighat; Panda, Siva S.; Ansari, Farzana Latif
Graphical abstract: Abstract: 1, 4-Disubstituted-1, 2, 3-triazoles were synthesized by Cu(I) catalyzed click reaction, where the azides, with electron donating and electron withdrawing groups acted as 1, 3-dipoles and 1-ethynyl-1-cyclohexanol served as the terminal alkyne. These synthesized triazoles were subjected to enzymatic assay which showed promising activity against α-glucosidase; 1-(2-cyano-4-nitrophenyl)-4-(1-hydroxycyclohexyl)-1 H -1, 2, 3-triazole3m being the most active members of the library. Molecular docking studies of these triazoles with the homology-modeled α-glucosidase protein were also performed to delineate ligand–protein interactions at molecular level which suggested that Phe157, Arg312 and His279 are the major interacting residues in the biding site of the protein and may have a significant role in the inhibition of enzyme's function.